The Effects of Glass Bubbles, Clay, Xanthan Gum and Starch Concentrations on the Density of Lightweight Biopolymer Drilling Fluid - Nee, L.S.; Mohamed Jan, B.; Si Ali, B.; Noor, I.M. (Trans Tech Publications, 2014)
It is an open secret that currently oil and gas industry is focusing on increasing hydrocarbon production through underbalanced drilling (UBD) and finding ways to ensure the drilling process is less harmful to the environment. Water-based biopolymer drilling fluids are preferred compared to oil based drilling fluids owing to the fact that it causes less pollution to the environment. This paper investigates the effects of varying concentrations of environmentally safe raw materials, namely glass bubbles, clay, xanthan gum and starch concentrations on the density of the formulated biopolymer drilling fluid to ensure that it is suitable for UBD. As material concentrations were varied, the density for each sample was measured at ambient temperature and pressure. Results showed that the final fluid densities are within acceptable values for UBD (6.78 to 6.86 lb/gal). It is concluded that the formulated water-based biopolymer drilling fluid is suitable to be used in UBD operation.